Understanding the Cellular and Molecular Mechanisms That Control Early Cell Fate Decisions During Appendicular Skeletogenesis - Marín-Llera, Jessica Cristina; Garciadiego-Cázares, David; Chimal-Monroy, Jesús (Frontiers in Genetics, 2019)
The formation of the vertebrate skeleton is orchestrated in time and space by a number of gene regulatory networks that specify and position all skeletal tissues. During embryonic development, bones have two distinct origins: bone tissue differentiates directly from mesenchymal progenitors, whereas most long bones arise from cartilaginous templates through a process known as endochondral ossification. Before endochondral bone development takes place, chondrocytes decide between two fates, cartilage or joint, and thus activate either the cartilage differentiation programme or the joint formation programme. Once the cartilage differentiation programme starts, the growth plate begins to form. In contrast, when the joint formation programme is activated, a capsule begins to form that contains special articular cartilage and synovium to generate a functional joint. In this review, we will discuss the mechanisms controlling the earliest molecular events that regulate cell fate during skeletogenesis in long bones. We will explore the initial processes that lead to the recruitment of mesenchymal stem/progenitor cells, the commitment of chondrocyte lineages and the formation of skeletal elements during morphogenesis. Thereafter, we will review the process of joint specification and joint morphogenesis. We will discuss the links between transcription factor activity, cell–cell interactions, cell–extracellular matrix interactions, growth factor signalling and other molecular interactions that control mesenchymal stem/progenitor cell fate during embryonic skeletogenesis.